Penerapan Protokol Kesehatan Covid-19 di Lingkungan Kerja dalam Perspektif Planned Behavioral Theory - Puspa Indah Pratiwi; Siswidiyanto, Siswidiyanto (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2023)
The purpose of this study was to determine the application of the Covid-19 health protocol in the work environment based on the Perspective of Planned Behavioral Theory in public organizations in East Java Province, Indonesia. Based on the analysis carried out, the results obtained that a) Attitude has a positive and significant effect on ASN behavior in implementing health protocols in the work environment in the